Audit identified modifiable factors in Hospital Care of Newborns in low-middle income countries: a scoping review - Ogola, M; Njuguna, EM; Aluvaala, J; English, M; Irimu, G (BioMed Central, 2022)
Background Audit of facility-based care provided to small and sick newborns is a quality improvement initiative that helps to identify the modifiable gaps in newborn care (BMC Pregnancy Childbirth 14: 280, 2014). The aim of this work was to identify literature on modifiable factors in the care of newborns in the newborn units in health facilities in low-middle-income countries (LMICs). We also set out to design a measure of the quality of the perinatal and newborn audit process.